Hygienic habits and living conditions of Romani population in the Sisak-Moslavina County - Galić Lukšić, Snježana (Array, 2020)
Aim. To establish the degree of consciousness of the importance of hygiene among the Romani population in the Sisak-Moslavina County and to examine whether there are differences in children’s health care of non-Romani population considering the number of hospitalized Romani children in general and especially regarding respiratory diseases. Methods. The study was conducted on 100 parents of hospitalized children, 50 of them being members of the Romani population and 50 being members of non-Romani population. It was done by means of a questionnaire specially designed for this study. The categorical data is represented by the absolute and relative frequencies, while the numerical data is described with the median and the limits of the interquartile span. Categorical variable differences were tested using Fisher’s exact test. The normality of numerical variable distribution was tested using the Shapiro-Wilk test. The differences in numerical variables between two independent groups were tested using the Mann-Whitney U test. Results. The results show that due to respiratory diseases a significantly large number of Romani children (43%) were hospitalized once in six months. Fewer children of Romani research subjects who have indoor plumbing were hospitalized. Romani families tend to visit a doctor when a child is injured or for a regular check-up rather than to seek a doctor’s advice. In non-Romani families, children tend to shower every day, have their own towel and better personal hygiene habits than children of Romani families. The results clearly show hygiene habits differ greatly between Romani and non-Romani families. Neglecting their children’s personal hygiene habits in Romani families points to a problem of insufficient education of the parents. Conclusion.